2020
DOI: 10.31557/apjcb.2020.5.2.35-41
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of Glutathione S-transferase and Cervical Cancer Susceptibility in Northeastern Thailand

Abstract: Background: Exposure to certain carcinogens together with host genetic predisposition likely has an influence on cervical carcinogenesis. Objective: Our aim was to evaluate synergistic effects of glutathione S-transferase (GST) polymorphisms and risk behaviors (i.e., smoking and contraceptive use) on squamous cell cervical cancer (SCCA) development in northeastern Thailand. Methods: Subjects were 198 (SCCA) patients and 198 age-matched healthy controls. Multiplex PCR and PCR-RFLP were used to determine GSTT1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Ma Ning [25] genotype data were incomplete, and the literature was excluded. Baseline characteristics and quality scores of references [20–53] are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Ma Ning [25] genotype data were incomplete, and the literature was excluded. Baseline characteristics and quality scores of references [20–53] are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The frequencies of genotype and allele of GSTA1 -69C>T polymorphism have been reported in diverse populations. The findings obtained for the Turkish population were compared with the results reported for various populations [4,6,8,9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25] as depicted in Table 2. Accordingly, GSTA1 -69T variant allele was more frequent in South Tunisians and Germans compared to other populations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, polymorphism in the glutathione Stransferase (GST) gene was reported, with the null genotype of GSTT1 resulting in a 3-and 4-fold increased risk of cervical cancer among cervical cancer patients who had a smoking partner and who used oral contraceptives, respectively. Furthemore, the heterozygous and null genotypes of GSTM1 were associated with a 2.6-and 1.7-fold increased risk of cervical cancer when compared with the respective wild-type (present) genotype [38]. Similarly, a meta-analysis reported that the null genotype of GSTM1 was associated with an increased risk of cervical cancer, particularly in the Indian and Chinese populations [39].…”
Section: Risk Factors Of Cervical Cancermentioning
confidence: 97%
“…In terms of the causes and necessary risk factors for cervical cancer in Thailand, HPV infection, especially type 16 and 18, remains the main cause of cervical cancer among Thai women, as in other countries [15][16][17][18]. Moreover, many studies have reported an association between risk factors and an increased risk of cervical cancer in Thai women, including exposure to, certain risk factors and genetic polymorphisms, such as VDR, CYP1A1, MDR, and GST [17,[31][32][33][34][35][36][37][38][39][40][41]. Finally, the COVID-19 pandemic resulted in an interruption to cervical cancer screening globally [55][56][57][58]68].…”
Section: Mayuree Wongpratate Et Al Cervical Cancer In Thailandmentioning
confidence: 99%